True Generalized Microdontia and Hypodontia with Spondyloepiphyseal Dysplasia - Anita Singhal; Parul Singhal; Ranjan Gupta; Kush Dev Jarial (Case Reports in Dentistry)
Spondyloepiphyseal dysplasia (SED) is a descriptive term used for group of inherited disorders of bone growth resulting in short stature, skeletal abnormalities, and problems with hearing and vision. SED have three major forms, SED congenital, pseudoachondroplastic SED, and SED tarda. SED tarda is milder than SED congenita. True generalized microdontia is a rare condition in which all the teeth are abnormally small. This is a report of a rare case having SED with generalized microdontia in a 26-year-old patient.